2021
DOI: 10.1093/jme/tjab121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of BG-Lures on the Male Aedes (Diptera: Culicidae) Sound Trap Capture Rates

Abstract: With global expansion of the two main vectors of dengue, Aedes aegypti (Linnaeus, Diptera: Culicidae) and Aedes albopictus (Skuse, Diptera: Culicidae), there is a need to further develop cost-effective and user-friendly surveillance tools to monitor the population dynamics of these species. The abundance of Ae. aegypti and Ae. Albopictus, and associated bycatch captured by Male Aedes Sound Traps (MASTs) and BG-Sentinel (BGS) traps that were unbaited or baited with BG-Lures were compared in Cairns, Australia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Also, Staunton et al . 21 did not observe any impact of BG-Lure on the catches of Ae. aegypti and Ae.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Also, Staunton et al . 21 did not observe any impact of BG-Lure on the catches of Ae. aegypti and Ae.…”
Section: Discussionmentioning
confidence: 64%
“…However, some studies have found that BG-Sentinel traps baited with CO 2 alone were able to catch significantly more individuals than BG-Sentinel traps baited with BG-Lure-coupled or not with CO 2 20 . Also, Staunton et al 21 did not observe any impact of BG-Lure on the catches of Ae. aegypti and Ae.…”
Section: Discussionmentioning
confidence: 91%
“…[19] However, some studies have found BG traps baited with CO 2 alone were able to catch signi cantly more individuals than BG traps baited with BG-Lure -coupled or not with CO 2 . [20] Also, Staunton et al [21] did not observe any impact of BG-Lure on the catches of Ae. aegypti and Ae.…”
Section: Discussionmentioning
confidence: 92%